2021
DOI: 10.1155/2021/4760249
|View full text |Cite
|
Sign up to set email alerts
|

Observer-Based Leader-Following Consensus of General Linear Multiagent Systems Based on Novel Event Trigger Mechanism with Input Time Delay under Directed Graphs

Abstract: This paper considers the tracking and containment consensus for the general linear systems with input time delays under directed communication networks. The distributed observer-based algorithm on the basis of event-triggering mechanism will be designed by using only neighboring agents information. In this way, we can save network resource effectively. The event-based protocol with input time delays will be proposed for the leader-follower systems. Appropriate feedback gain matrices and trigger parameters can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Remark 3: From the proof process, especially (15), it can be concluded that Theorem draws the conclusion that the observers (5) can finally precisely track the agents' states via the protocol (6). This is what makes our work different from others.…”
Section: A An Estimator-based Approachmentioning
confidence: 90%
See 3 more Smart Citations
“…Remark 3: From the proof process, especially (15), it can be concluded that Theorem draws the conclusion that the observers (5) can finally precisely track the agents' states via the protocol (6). This is what makes our work different from others.…”
Section: A An Estimator-based Approachmentioning
confidence: 90%
“…Accordingly, the consensus is achieved by the protocol. Different from existing results such as [15], the trigger function in this article is based on observer errors, and parameters is design-able and adjustable. These features alleviate the use of computation resources and communication bandwidth.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations